The Effect of Green Finance and Leverage on Company Value with Profitability as a Mediating Variable - Hidayat, Ilham; Bailusy, Muhsin N; Rusandry, Rusandry (IJBLE Scientific Publications Community Inc., 2026)
This study aims to determine and analyse the effect of green finance and leverage on company value with profitability as a mediating variable. The object of this study is mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. This study uses a purposive sample of 14 companies. The data used are secondary, obtained from annual reports, sustainability reports, and company financial reports for four consecutive years. The data analysis method used in this study is Structural Equation Modelling–Partial Least Squares (SEM-PLS), with data processing techniques using SmartPLS 4.0 software. The results of the survey indicate that green finance has a significant effect on company value; leverage has a significant effect on company value; green finance does not have a substantial effect on profitability; leverage has a significant effect on profitability; and profitability affects company value. In addition, profitability does not mediate the effect of green finance on company value, nor does it mediate the effect of leverage on company value.